Efektivitas Program Pembelajaran di TPA Masjid Al-Ilham Karanglo dalam Meningkatkan Minat Belajar Al-Qur'an Anak - Kun Zakia Khoirotun Nisa; Zahra Ar Rohmatic; Qodim Ma'shum (PT. Nawa Edukasi Nusantara, 2026)
This study aims to analyze the effectiveness of the learning program at TPA Masjid Al-Ilham Karanglo in improving children’s interest in learning the Qur’an. This research was motivated by the low interest of children in learning the Qur’an due to the influence of technological development, monotonous learning methods, and the lack of varied learning activities. This study used a descriptive qualitative approach with data collection techniques through observation and interviews. The research subjects consisted of TPA administrators, teachers from UKMI Nurul Ilmi UIN Raden Mas Said Surakarta, and students of TPA Masjid Al-Ilham Karanglo. The learning program was conducted three times a week, namely on Monday, Wednesday, and Saturday from 4:00 p.m. to 5:00 p.m. The activities included reading Iqro’ and the Qur’an, memorizing daily prayers, reviewing short surahs, educational videos, fun games, rewards, prayer recitation learning, and outbound activities. The results showed that the learning program at TPA Masjid Al-Ilham was quite effective in increasing children’s interest in learning the Qur’an. This was indicated by the increased enthusiasm, participation, and active involvement of students during the learning process. The use of interactive and enjoyable learning methods was able to create a more conducive learning atmosphere so that children became more motivated to learn the Qur’an. Although there were obstacles such as differences in reading abilities and the influence of gadget use, the learning program still contributed positively to children’s reading skills, memorization abilities, and religious character building.